Using Family Taxon as an Indicator of Haram Halal of Reptiles in Animal Systematic Lab Work - Sutriyono Sutriyono (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2020)
Haram halal of an animal are usually refer to the four mahzab in Islamic believe. This study discussed about halal haram of reptile class that will would be connected with its taxon family as an indicator. This research aims to set the family taxon as an indicator in determining halal haram of reptiles Literature study was done, tracing the written manuscript of Islamic and Science journals, books, websites or other relevant sources that can be used as a reference. The study showed that if a species in the family taxon is classified as halal to the Islamic Law, then the rest of the members in the family were considered as halal.